Perception of Japanese Physicians about Human Papillomavirus Vaccine. (4th October 2017) - Katsuta, Tomohiro; Moser, Charlotte; Offit, Paul; Feemster, Kristen
Abstract: Background: Current vaccination coverage of Human Papillomavirus vaccine (HPVV) in Japan is less than 1% because the Ministry of Health, Labour and Welfare (MHLW) suspended its proactive recommendations for HPVV in 2013 after some reports of possible adverse events following immunization. We evaluated the perception of Japanese physicians about HPVV in order to consider the appropriate countermeasure to improve HPVV coverage in Japan. Methods: We conducted a cross-sectional study using a postal questionnaire targeting 330 Japanese physicians (78 pediatricians, 225 internists and 27 obstetricians-gynecologists (OB-GYNs)) in Kawasaki, Japan in 2016. The questionnaire comprised questions about education frequency, physicians' perception and recommendation behavior related to adolescent vaccines (HPVV, diphtheria tetanus toxoid (DT) and inactivated influenza vaccine (IIV)). Results: Valid responses were obtained from 148 (44.9%) physicians (pediatricians 80.8%, internists 31.6% and OB-GYNs 51.9%). Very few (8.0%) of physicians provided HPVV during the past month. Only 21.3% of physicians educated aggressively about HPVV, which was significantly less frequently than DT (61.7%) and IIV (88.6%). Similarly, 53.1% of physicians recommended HPVV aggressively, which was significantly less frequently than DT (83.1%) and IIV (80.3%). We found no significant differences in the frequency of HPVV education or recommendation by pediatricians, internists and OB/GYNs (22.4% vs. 16.9% vs. 35.7% and 54.8% vs. 47.9% vs. 71.5%, respectively). However, 90.0% of physicians answered that if MHLW were to reinstate its HPVV recommendation, they would more aggressively recommend HPVV for adolescents. Conclusion: Although Japanese physicians were cautious about HPVV and infrequently provided education or made a recommendation for HPVV compared with other adolescent vaccines, our survey suggested such a passive attitude could be improved by the MHLW resuming its proactive recommendation in Japan. Disclosures: All authors: No reported disclosures.